Ports 2019. papers from sessions of the 15th triennial international conference, September 15-18, 2019, Pittsburgh, Pennsylvania - Jain, Pooja; Stahlmann, William S., III (American Society of Civil Engineers, 2019)
This collection contains 77 peer-reviewed papers on current topics in port engineering, highlighting the role of ports as engines of economic development and as stewards of environmental resources. Topics include: structural and geotechnical considerations in ports; facilities inspection, repair, and maintenance; seawall and pier construction and maintenance; coastal and sea level rise; seismic events and retrofit; tsunamis, storm surge, and waves; port design standards; equipment and systems automation; and case studies. These papers will be of interest to both practitioners and researchers in the area of port and harbor planning and development.
"Sponsored by PIANC, Ports and Harbors Committee of the Coasts, Oceans, Ports, and Rivers Institute of the American Society of Civil Engineers."
Keywords: Harbors -- Design and construction -- Congresses.; Harbors -- Maintenance and repair -- Congresses.; Earthquake hazard analysis -- Congresses.; Harbors -- Environmental aspects -- Congresses.; Flood damage prevention -- Congresses.; Waterfronts -- Design and construction -- Congresses.; Waterfronts -- Maintenance and repair -- Congresses.; elektronické knihy; electronic books